On some inequalities with Fibonacci numbers via weighted reverse Hölder inequalities - Perušić Pribanić, Anamarija (Annales Mathematicae Silesianae, 2026)
In this paper, we introduce new inequalities for weighted sums of powers. By utilizing known Fibonacci identities alongside our generalized inequalities, we derive new sequences of inequalities for Fibonacci numbers.